Influência da periodontite apical no perfil hematológico de ratos Wistar portadores de insuficiência renal aguda - Costa, Taís Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The objective of this study was to verify the influence of apical periodontitis (AP) on the hematological profile of rats with acute renal failure (ARF). Thirty two rats were divided into four groups (n = 8): Group C - control rats; AP group - rats with apical periodontitis; Group IRA - rats with acute kidney injury; IRA + AP group - rats with acute kidney injury and apical periodontitis. IRA was induced by daily application of Gentamicin (100mg/kg/day) for 8 days intraperitoneally. The AP was induced by means of pulp exposure of the first and second upper and lower right molars and was confirmed radiographically after 15 days. After this period, hematological tissue was collected by means of a cardiac puncture for the analysis of the 13 hemogram parameters (Hemacic, Globular Volume, Hemoglobin, MCV, MCHC, Leukocytes, Neutrophils, Lymphocytes, Monocytes, Eosinophils, Basophils and Total Plasma Protein). The data were tabulated and subjected to statistical analysis (p<0.05). The radiographic analysis was performed through bone resorption along with the exposure of the teeth submitted to the pulp exposure. The increase was significant in leukocytes, lymphocytes and neutrophils, (p<0.05), in the ARF and ARF + AP groups in relation to the control group. In addition, the red series in the IRA and IRA + AP groups. The MCV significantly reduced (p<0.05), mainly in the ARF + AP group. A study was performed of multiple foci of apical periodontitis when associated with ARI, leading to changes in parameters in the blood profile that cause disturbances in the metabolism. Clinical relevance: the presence of endodontic infections can interfere with the blood profile, altering systemic health

O objetivo deste trabalho foi verificar a influência da Periodontite apical (PA) no perfil hematológico de ratos portadores de insuficiência renal aguda (IRA). Foram utilizados 32 ratos divididos em 4 grupos (n=8): Grupo C - ratos controle; Grupo PA - ratos portadores de PA; Grupo IRA - ratos portadores de IRA; Grupo IRA+PA - ratos portadores de IRA e PA. A IRA foi induzida por meio de uma aplicação diária de Gentamicina (100mg/Kg/dia) por 8 dias, via intraperitoneal. A PA foi induzida por meio de exposição pulpar dos primeiros e segundos molares superiores e inferiores do lado direito e foi confirmada radiograficamente após 15 dias. Decorrido este período, foi feita a coleta do tecido hematológico, por meio de punção cardíaca, para análise dos 12 parâmetros do hemograma (Hemácias, Volume Globular, Hemoglobina, VCM, CHCM, Leucócitos, Neutrófilos, Linfócito, Monócito, Eosinófilo, Basófilo, e Proteína Plasmática Total). Os dados foram tabulados e submetidos à análise estatística (p<0,05). Na análise radiográfica foi observada reabsorção óssea junto ao periápice dos dentes submetidos à exposição pulpar. No sangue foi observado aumento significativo de leucócitos, linfócitos e neutrófilos (p<0,05), nos grupos IRA e IRA+PA em relação ao grupo controle. Além disso, houve diminuição da série vermelha (p<0,05) nos grupos IRA e IRA+PA. O VCM reduziu significantemente (p<0,05) principalmente no grupo IRA+PA. Foi concluído que a presença de múltiplos focos de periodontite apical quando associada à IRA, levam a alterações de fatores no perfil sanguíneo que causam distúrbios no metabolismo. Relevância clínica: A presença de infecções endodônticas pode interferir no perfil sanguíneo, alterando a saúde sistêmica
Keywords: Periodontite periapical; Lesão renal aguda; Contagem de células sanguíneas; Ratos Wistar; Periapical periodontitis